Five Questions on International Migration and Development - Özden, Çağlar; Rapoport, Hillel; Schiff, Maurice (World Bank, 2013)
The movement of people in search of better economic conditions and a more secure environment is as old as human history. Such movements not only profoundly affect the lives of the migrants, but also lead to significant economic and social transformations in migrants' countries of origin and destination. In recent years, a significant increase in the growth of international migration and remittance flows and in awareness of their development impact has led to a resurgence of interest by academics, policymakers, and analysts in what has been referred to as the third leg of globalization (the other two being international trade and international capital flows).